2014
DOI: 10.1186/preaccept-2130575587130627
|View full text |Cite
|
Sign up to set email alerts
|

Bat guano as new and attractive chitin and chitosan source

Abstract: Introduction: Chitin is a biopolymer that forms the exoskeleton of arthropods, and is found in the cell walls of fungi. It has a wide range of uses in fields such as cosmetics, pharmacy, medicine, bioengineering, agriculture, textiles and environmental engineering based upon its nontoxic, ecofriendly, biocompability and biodegradability characteristics. Commercially, chitin is obtained from processing the outer skeleton of Crustacea such as shrimp, crab, prawn and crayfish after they have been consumed as food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this study the FTIR peaks measured for Chilopoda chito san were at 1655 and 1584 cm -1 . In other studies, these bands were observed between 1651 and 1656 and 1584 and 1590 cm -1 , respectively, for the commercial chito san [30,31]. When the chitosan from S. cingulata were compared with commercial chitosan, it is seen that they were quite similar to each other.…”
mentioning
confidence: 64%
“…In this study the FTIR peaks measured for Chilopoda chito san were at 1655 and 1584 cm -1 . In other studies, these bands were observed between 1651 and 1656 and 1584 and 1590 cm -1 , respectively, for the commercial chito san [30,31]. When the chitosan from S. cingulata were compared with commercial chitosan, it is seen that they were quite similar to each other.…”
mentioning
confidence: 64%
“…And it is worth mentioning that chitosan has a number of notable properties, including nontoxicity, highly porous and fibrous structures, biocompatibility, anti-inflammatory, antimicrobial activities and wound healing promoter (e.g., fibroblast activation, cytokine production, giant cell migration and stimulation of type IV collagen synthesis) [26][27][28][29][30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%